Technical Aspects of Web Photography as a Medium of Tourism Development - Ptiček, Petra (Array, 2021)
Information and communication technology is an important factor for national, regional and local sustainable tourism development according to the long-term Croatian national strategic plan. New forms of information, such as web sites; new media, materials, political and social change, all influence tourists" decisions when choosing specific destinations. The aim of this research is to determine, based on the analysis of the tourism media campaign, the relationship between new communication trends and the application of photography as a medium that influences the experience when choosing a destination and the importance of crucial information factors on web pages based on their technical and visual characteristics.